Short-term safety, function, and quality of life in patients treated with Univers Revers prosthesis: a multicenter 2-year follow-up case series - Schwyzer, Hans-Kaspar; Marzel, Alex; Wirth, Barbara; Rickenbacher, Dominik; Flury, Matthias; Schoch, Christian; Tauber, Mark; Rzepka, Daniel; Lehmann, Lars; Lichtenberg, Sven; Magosch, Petra; Habermeyer, Peter; et al. (Journal of shoulder and elbow surgery, 2020)
Background - The use of reverse total shoulder arthroplasty (RTSA) has dramatically increased in recent years with the advent of new prosthesis designs regularly entering the market. We define the rate of local complications during the first 2 years after RTSA with the Univers Revers prosthesis and describe the changes in radiologic outcomes, as well as function, pain, satisfaction, and quality of life. - Methods - This multicenter, prospective case series included rotator cuff tear arthropathy patients who underwent RTSA with the Univers Revers. Incidence percentages of complications and pathologic radiographic changes were documented. Mixed-model linear regression was used to examine changes in range of motion, shoulder function (Constant score, Shoulder Pain and Disability Index, Subjective Shoulder Value), and quality of life (EQ-5D-5L [European Quality of Life 5 Dimensions 5 Level] and EQ-VAS [EuroQol Visual Analog Scale]). - Results - Of 187 patients, 59.4% were women, and the mean age was 75.3 years (range, 56-91 years). Twenty-five percent of patients had a postoperative complication; 5 complications were severe (2.7%, 5 of 187), whereby 2 were implant related (1.1%; 95% confidence interval [CI], 0.1%-3.8%). The incidence of scapular notching was 10.6% (95% CI, 6.5%-16%). After 2 years, abduction, flexion, and abduction strength improved by 54° (95% CI, 50°-58°), 57° (95% CI, 53°-60°), and 5 kg (95% CI, 4-5 kg), respectively (P < .001), whereas external rotation at 0° (1°; 95% CI, -1° to 3°) did not improve (P = .4). The Constant score improved by 39 (95% CI, 38-41); Shoulder Pain and Disability Index, by 50 (95% CI, 47-52); and Subjective Shoulder Value, by 43 (95% CI, 41-45) (P < .001). Furthermore, the EQ-5D-5L index value improved by 0.31 (95% CI, 0.30-0.33), and the EQ-VAS score improved by 16 (95% CI, 14-18) (P < .001). - Conclusion - Our case series showed a low complication rate with a consistent clinically relevant and statistically significant improvement across most clinical and patient-reported outcomes for the Univers Revers. Long-term safety requires further investigation.
Gesehen am 08.08.2024